Eligibility for late endovascular treatment using DAWN, DEFUSE-3, and more liberal selection criteria in a stroke center. (26th November 2019) - Nannoni, Stefania; Strambo, Davide; Sirimarco, Gaia; Amiguet, Michael; Vanacker, Peter; Eskandari, Ashraf; Saliou, Guillaume; Wintermark, Max; Dunet, Vincent; Michel, Patrik
Abstract : Background and purpose: The real-life application of DAWN and DEFUSE-3 trials has been poorly investigated. We aimed to identify the proportion of patients with acute ischemic stroke (AIS) eligible for late endovascular treatment (EVT) in our stroke center based on trial and more liberal selection criteria. Methods: All consecutive patients in our stroke registry (2003–2017) admitted within 5–23 hours of last proof of good health were selected if they had complete clinical and radiological datasets. We calculated the proportion of patients eligible for late EVT according to trial (DAWN and/or DEFUSE-3) and more liberal clinical/imaging mismatch criteria (including lower admission National Institutes of Health Stroke Scale score and Alberta Stroke Program Early CT Score for core estimation). Results: Of 1705 patients with AIS admitted to our comprehensive stroke center in the late time window, we identified 925 patients with complete clinical and radiological data. Among them, the proportions of late EVT eligibility were 2.5% (n=23) with DAWN, 5.1% (n=47) with DEFUSE-3, and 11.1% (n=103) with more liberal criteria. Considering late-arriving patients with large vessel occlusion (n=221), the percentages of eligible patients were 10.4%, 21.3%, and 46.6%, respectively. A favorable outcome was observed at comparable rates in treated patients selected by trial or liberal criteria (67% vs 58%, p=0.49). Conclusions: In a long-term stroke registry, the proportion of late EVT eligibility varied greatly according to selection criteria and referral pattern. Among late-arriving patients referred to our comprehensive stroke center, we found 5.6% eligible according to trial (DAWN/DEFUSE-3) and 11.1% according to liberal criteria. These data indicate that late EVT could be offered to a larger population of patients if more liberal criteria are applied.